A Systematic Review of the Potential of Cold Compresses Therapy: Strategy for Preventing Hematoma and Alleviating Pain in Post Cardiac Catheterization Patients - Sugiharto F; Yusanti I; Sari WP; Yuliandani E; Kosasih CE; Trisyani Y; Priambodo AP; Nuraeni A; Anna A; Emaliyawati E; Mirwanti R (Journal of Pain Research)
Firman Sugiharto,1 Irma Yusanti,1 Wulan Puspita Sari,1 Erin Yuliandani,1 Cecep Eli Kosasih,2 Yanny Trisyani,2 Ayu Prawesti Priambodo,2 Aan Nuraeni,2 Anastasia Anna,2 Etika Emaliyawati,2 Ristina Mirwanti2 1Master Study Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Critical Care and Emergency Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Cecep Eli Kosasih, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, Indonesia, Tel +6281320941727, Fax +622287793411, Email cecep.e.kosasih@unpad.ac.idBackground: Patients still frequently report complications after cardiac catheterization procedures, such as hematoma and pain. These complications increase the length of stay and hospital costs. Several studies have determined cold compress therapy’s effectiveness in preventing hematomas and reducing pain in patients after cardiac catheterization. However, to date, no review study has synthesized this comprehensively.Purpose: This review aimed to explores the potential of cold compress therapy as a strategy for preventing hematoma and alleviating pain in post-cardiac catheterization patients.Methods: Systematic review was reported based on the PRISMA Extension. A literature search used relevant keywords from six primary databases, such as CINAH Medline Plus, PubMed, ScienceDirect, Scopus, Taylor and Francis, and one search engine, Google Scholar. The quality of evidence was assessed using the Joanna Briggs Institute critical appraisal checklist and Risk of Bias. Data synthesis was used thematically with an explorative, descriptive approach.Results: This review found and analyzed twelve articles. Based on the results of the analysis, cold compress therapy for 15 to 20 minutes can potentially prevent hematomas and reduce pain in patients after cardiac catheterization.Conclusion: This review concludes that cold compress therapy can potentially prevent hematomas and reduce pain in this population. Health workers, especially nurses, can consider cold compress therapy as a strategy in the nursing care program for patients after cardiac catheterization.Keywords: cardiac catheterization, cold compress, coronary heart disease, hematoma, pain